Analysis of AC-AC Converter Based Dynamic Voltage Restorer for Maintaining Power Quality in the Transmission Line - Tamilvanan G.; Mahendran S. (Institute of Advanced Engineering and Science, 2016)
In the power system the major issue is to maintain the power quality .The term of power quality is to maintain the disturbance less voltage to the power system. The voltage disturbance mainly caused by voltage sag, voltage swell and harmonics presented in the system. If the system voltage is going below to the nominal voltage, then it is called as voltage sag. These power quality (PQ) events typically last for less than one second. If the system voltage is going above the nominal voltage, there it is called as voltage swell. The AC-AC converter based DVR is proposed. It can properly compensate for unlimited time duration, balanced, and as well as unbalanced voltage sag by observing the power from the grid. The pulse width modulation technique is used to triggering the switches. Only by the simple Bidirectional switches were used for generate the compensation voltage.